HOMOEOPATHY AND ITS APPLICATION IN CASES OF RHEUMATOID ARTHRITIS - Dr. Mitul Lathiya; Dr. Vikrant A. Tungar; Dr. Rajendra C Ashra; Dr. Sweta R. Panchani4 (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Rheumatoid arthritis is a chronic autoimmune disorder that causes inflammation and pain in the joints, leading to significant disability and reduced quality of life for affected individuals. Traditional treatment approaches often involve the use of nonsteroidal anti-inflammatory drugs (NSAIDs) and disease-modifying antirheumatic drugs (DMARDs). However, there is growing interest in alternative therapies such as homeopathy. This study aims to assess the efficacy of homeopathic treatment in rheumatoid arthritis by analysing existing literature and research findings. The findings suggest that homeopathic interventions may have a positive impact on symptom management, pain relief, and overall well-being in patients with rheumatoid arthritis. However, more rigorous research studies are needed to establish a stronger evidence base and to determine the mechanisms of action underlying homeopathic treatments for this condition.